Pengembangan Game Edukasi Pengenalan Makanan Sehat Menggunakan Kinect - Iqbal Firmansyah; Muhammad Aminul Akbar; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Healthy food are food that hygienic and contain balanced nutrients needed by the body. In 2013 the national malnutrition rate in children aged 5-12 years is still high, that is the prevalence of lean 11.2 percent, the short prevalence 30.7 percent, and the prevalence of obese 18.8 percent. It's necessary for introduction of healthy foods as a step to reduce malnutrition level. Introduction method can be done with learning through educational games, so that the learning process is more fun and get more effective results. The game will be titled "Makanan Sehat" which will introduce and teach children about the basis of healthy food according to the guide â€œPedoman Gizi Seimbang (PGS)â€ with kinect based learning method on PC (Personal Computer) platform. Pedoman gizi seimbang is a guide to living healthy including good rules of food consumption which is an improvement of slogan â€œ4 sehat 5 sempurnaâ€. The use of kinect in the game is expected to increase the pleasure in play and learn more effectively. Game testing is done to 10 children ages 5-12 years with method fun testing. Fun testing to test the level of pleasure in playing the game, which resulted in 10 respondents agreed the use of kinect impact at the fun of playing the game.